O’Neil-type inequalities for convolutions in anisotropic Lorentz spaces - Tleukhanova, Nazerke; Sadykova, Kelbet (Eurasian Mathematical Journal, 2019)
In this paper we study the boundedness of convolutions in the anisotropic Lorentz spaces.